Influence of stress on cellular immunity in patients with autoimmune thyroid pathology - Yu.I. Karachentsev; O.A. Goncharova; V.M. Dubovyk; L.V. Gerasymenko; K.O. Pobelensky (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Autoimmune thyroid diseases (AITDs), which include diffuse toxic goiter (DTG), or Graves’ disease, and autoimmune thyroiditis (AIT), are the most common organ-specific autoimmune diseases. Since recently the population of Ukraine is in a state of chronic stress associated with military operations on the territory of our country, it is important to clarify the nature of stress impact on cellular immunity in patients with autoimmune thyroid pathology. The purpose of the study was to establish the features of the cellular link of the immune response to stress in patients with autoimmune thyroiditis and diffuse toxic goiter. Materials and methods. Sixty patients with AITDs were examined in the clinic of V. Danilevsky Institute for Endocrine Pathology Problems of the National Academy of Medical Sciences of Ukraine, 32 patients with AIT and 28 with DTG. In 24 cases, AITDs were newly diagnosed during the armed conflict (12 patients with DTG and 12 patients with AIT), and in 36 cases, the disease had a long course (16 patients with DTG and 20 patients with AIT, the manifestation took place until 2022). The relative (%) levels of CD3, CD4, CD8, CD16 and CD22 were determined in order to characterize immune homeostasis in patients with AITDs. Immunoregulatory indices were calculated as integral criteria of regulatory and effector links of immunity: suppression — CD4/CD8 as one of the key indicators of immune status, as well as indices of B cell help — CD4/CD16 and CD8/CD16. Results. The presence of DTG newly diagnosed in wartime is accompanied by a significant decrease in CD3 compared to the long-term course (55.67 ± 1.08 vs. 59.12 ± 1.14, P < 0.05). At the same time, in the group of patients with AIT newly diagnosed during military operations, a decrease in CD3 was less pronounced than on the background of DTG (58.30 ± 2.12 vs. 55.67±1.08). The wartime factor contributes to a more pronounced decrease in CD3 against the background of DTG versus AIT (55.67 ± 1.08 vs. 58.30 ± 2.12). Against the background of DTG and AIT in subgroups with newly diagnosed disease, CD4 levels were higher than in the long-term course (36.33 ± 1.47 vs. 38.87 ± 1.12 in DTG and 35.35 ± 1.08 vs. 36.33 ± 1.47 in AIT). CD16 was lower in patients with DTG when the disease was detected during military operations and probably differed from the group with a long course of the disease (16.58 ± 0.94 vs. 18.68 ± 0.82, Р < 0.05). CD22 level was significantly lower in patients with DTG newly diagnosed during the war than at the long course (20.00 ± 1.01 vs. 23.19 ± 1.09, P < 0.05). The groups of patients with AIT or DTG newly diagnosed during the war had no significant difference in the levels of CD22 but on the background of AIT, the indicators were higher than in DTG (22.53 ± 1.41 vs. 20.00 ± 1.01). At the same time, with a long course of AIT and DTG, CD22 levels were higher in the DTG group (21.65 ± 1.58 vs. 23.19 ± 1.09). Conclusions. In patients with DTG and AIT, indicators of the cellular immune response have a multidirectional orientation, which depends, among other things, on the time of the disease and the stress that caused it. Immunoregulatory indices of suppression and B cell help significantly differ depending on the type of autoimmune disease and the time of its manifestation.